Understanding and managing groundwater impacted by historical mining beneath the city of Bendigo - Hoban, M; Trotter, N (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Bendigo has a long history of mining which has left an extensive network of over 5,000 mine shafts and underground mine workings beneath urban areas of Bendigo. This is the largest concentration of deep gold mining shafts anywhere in the world. Bendigo is the third largest city in the state of Victoria, Australia, with a population of 121,000. Groundwater underneath Bendigo seeps into these workings, where it becomes contaminated with elevated levels of arsenic and metals. The groundwater is odorous due to the emission of hydrogen sulphide. If left unmanaged the supressed deep groundwater levels will recover and will discharge into Bendigo Creek which passes through the centre of Bendigo, impacting the water quality of the creek and producing odour which impacts public amenity. To maintain dry underground conditions during mining operations, groundwater was historically pumped from the workings thereby lowering local groundwater levels and preventing discharges to the environment (surface water). However, when the recent phase of mining ceased in 2011 dewatering activities were scaled back and as a consequence, water levels within the mine voids started recovering. To address the imminent risk of discharge, the Victorian Government approved an interim solution which initially pumped and treated mine-impacted water from a depth of 260 m beneath surface at the Central Deborah Gold Mine tourist attraction. The intervention also enabled the historic Central Deborah Gold Mine to continue providing underground tours. Since then, extensive technical assessment has been conducted involving experts in geochemistry, hydrogeology, hydrology, ecology and water treatment to get a detailed understanding of the conditions and develop a practical, sustainable long-term management approach. In addition to the technical work, consultation was also undertaken with traditional owners, community, stakeholders, economists and regulators to understand broader social, economic and regulatory aspects to the complex issue.
Keywords: groundwater